Redefining the Smart City: Culture, Metabolism and Governance. Case Study of Port Louis, Mauritius - Allam, Mohammad Zaheer (Curtin University, 2018)
This thesis of 8 publications explores how Smart Cities can move away from the corporate agenda of ICT consortiums supporting modernist new towns. A proposed Smart City Framework integrates sustainability principles using Culture, Governance and Metabolism to better achieve the UN urban agenda. This is then applied to the city of Port Louis, Mauritius, to enable urban regeneration of the old city to be enabled.